Analysis of Optic Nerve in Adults With Amblyopia Using OCTA - Lu, Hui; Zhang, Tonggang; Yue, Tao; Li, Xiaoqin; Ma, Bingfen; Liu, Hongxia (Frontiers in Medicine, 2022)
Abstract OBJECTIVE The aim was to quantify and compare papillary and peripapillary vessel density in amblyopic eyes of adults and age-matched controls. METHODS This cross-sectional study involved 20 eyes from 10 subjects with anisometropic amblyopia and 12 eyes of 6 age- and gender-matched healthy controls. Optical coherence tomography angiography (OCTA) was performed to all participants. SPSS (Statistical Package for the Social Sciences) 20 was used for data analysis. RESULTS Mean subject age was 35.70± 10.04 years (range 18-47) in the amblyopia group and 34.67±6.92 years( range 23-42) in the control group.The diopter of amblyopia ranges from + 3.00ds to + 5.00ds.The mean inside optic disk capillary vessel density（CVD） was 41.88±6.55 % in amblyopic eyes, 49.23±6.55 % in fellow eyes, and 50.23±4.00 % in control eyes (p < 0.05）. The mean inside optic disk all vessel density (AVD) was 52.97±6.71 % in amblyopic eyes, 59.87±4.59 % in fellow eyes, and 60.45±2.80 % in control eyes (p < 0.05）. The amblyopic eye of participants showed a decrease vessel density in the inside optic disk than in the fellow eyes and healthy subjects . CONCLUSIONS Our present study revealed lower vessel density inside the optic disc of adult patients with anisometropic amblyopia. But, further studies are really needed to determine the clinical relevance of this finding.